The Effect of Social Media Marketing, E-Wom, and Store Atmosphere on Consumer Purchasing Decisions - Nadeak, Beatrice Sarah Natalia; Sukarno, Agus (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine the effect of Social Media Marketing, Electronic Word of Mouth (e-WOM), and Store Atmosphere on Purchasing Decisions of Lestari Corner Coffee Yogyakarta. The data collection technique used is non probability sampling with purposive sampling technique. The data analysis method in this study uses multiple regression analysis techniques using SPSS 23. This research is casual associative research using a quantitative approach. The population in this study were all consumers who had visited Lestari Corner Coffee Yogyakarta. The number of samples used in this study were 100 respondents. The results of this study reveal that Social Media Marketing, Electronic Word of Mouth, and Store Atmosphere together have a positive and significant effect on Purchasing Decisions, Social Media Marketing has a positive and significant effect on Purchasing Decisions, Electronic Word of Mouth has a positive and significant effect on Purchasing Decisions, Store Atmosphere has a positive and significant effect on Purchasing Decisions.